Peran Pendidikan Agama Islam Dalam Membentuk Sikap Kemandirian Melalui Metode Peer Tutoring (Tutor Sebaya) Di SMK Sultan Agung 1 Tebuireng - Lathiefatul Aghniyah; Jumari Jumari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research discusses the role of Islamic Religious Education Teachers in Forming an Attitude of Independence Through the Peer Tutoring Method at Sultan Agung 1 Tebuireng Vocational School. The teacher's role is not only about understanding religious values, but also about developing critical thinking skills and instilling responsibility and discipline. Peer tutoring can make learning easier, actively participate in learning. Based on the problems above, this researcher has 3 objectives related to the research focus. The role of Islamic Religious Education Teachers in forming an attitude of independence through the peer tutoring method (Peer Tutor) at SMK Sultan Agung 1 Tebuireng. The research objectives are 1). To describe the role of teachers. The role of Islamic teachers in forming independence at SMK Sultan Agung 1 Tebuireng. 2). To describe the peer tutoring method at SMK Sultan Agung 1 Tebuireng. 3). To describe the role of Islamic Religious Education teachers in forming an attitude of independence through the peer tutoring method at SMK Sultan Agung 1 Tebuireng. The type of research is case study research. The research was carried out using a qualitative approach with descriptive methods. Data collection was carried out using observation, interview and documentation techniques. The informants in this research consisted of the school principal, head of student affairs, PAI teachers, and students. Data collected for observations and interviews were analyzed using data source triangulation analysis techniques. The results of this research show that, 1) The role of Islamic Religious Education teachers is very much needed, with the role of Islamic religious education teachers it can produce students who have good morals, have a sense of responsibility and discipline. 2) In learning, the teacher creates a peer tutoring method where students share their themes with each other so that learning becomes easy to understand with their peers. 3) Supporting factors that influence the role of Islamic religious education teachers using the peer tutoring method are good cooperation with students, communication skills, lack of seriousness in practicing this method, because sometimes they end up playing with their friends next to them, limited time. making one of the inhibiting factors, namely the lack of enthusiasm in participating in learning.